2021
DOI: 10.4103/ijem.ijem_145_21
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality Assessment in Adolescents with and without Type 1 Diabetes Using the Pittsburg Sleep Quality Index

Abstract: Background and Aims: Many diseases, especially chronic diseases, can lead to sleep disturbances. Our study aimed to evaluate sleep characteristics and the relationship between sleep disorders and diabetes-related variables in type 1 diabetes adolescents and to compare these results with a non-diabetic group of similar age and gender. Methods: This cross-sectional study collected data from 40 healthy adolescents and 50 patients of the same age group with type 1 diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Reduced slowwave sleep is associated with reduced self-management of diabetes, poor glycemic control, greater daytime sleepiness and poor quality of life [10]. Nonetheless, a recent study [11] carried out in a group of adolescents with T1DM and their peers showed that the prevalence of sleep disorders in T1DM patients was not higher than in the non-diabetic population, but girls in the latter group had significantly poor sleep quality. The sleep disturbances and the development of psychosocial illness in diabetic children can lead to non-adherence to treatment, increased risk of complications and deterioration in the quality of life [12].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced slowwave sleep is associated with reduced self-management of diabetes, poor glycemic control, greater daytime sleepiness and poor quality of life [10]. Nonetheless, a recent study [11] carried out in a group of adolescents with T1DM and their peers showed that the prevalence of sleep disorders in T1DM patients was not higher than in the non-diabetic population, but girls in the latter group had significantly poor sleep quality. The sleep disturbances and the development of psychosocial illness in diabetic children can lead to non-adherence to treatment, increased risk of complications and deterioration in the quality of life [12].…”
Section: Introductionmentioning
confidence: 99%